A NbO-type copper metal–organic framework decorated with carboxylate groups exhibiting highly selective CO2 adsorption and separation of organic dyes. Issue 36 (25th August 2016) - Liu, Xiuping; Xiao, Zhenyu; Xu, Jing; Xu, Wenbin; Sang, Pengpeng; Zhao, Lianming; Zhu, Houyu; Sun, Daofeng; Guo, Wenyue
Abstract : A porous Cu metal–organic framework (1 ) based on a pentacarboxylate ligand and paddlewheel SBU was synthesized and structurally characterized. Abstract : A porous Cu metal–organic framework (1 ) based on a pentacarboxylate ligand and paddlewheel SBU was synthesized and structurally characterized. Complex1 possesses a NbO-type framework with uncoordinated –COO − groups, resulting in its good selectivity for CO2 /N2 (36) and CO2 /CH4 (12) as well as a large CO2 -uptake capacity of 140 cm 3 g −1 at 273 K and 1 bar. Grand Canonical Monte Carlo (GCMC) simulations revealed that strong CO2 adsorption sites exist near the open Cu II sites and the uncoordinated –COO − groups. Significantly, complex1 exhibits water resistance and selective adsorption of cationic methylene blue (MB + ) in aqueous solution and the adsorbed MB + can be released in saturated NaCl solution, making it also a promising porous material for charge and pore-size dependent large-molecule capture and separation. The existence of coordinatively unsaturated metal sites as well as the exposed –COO − groups in the framework of1 is responsible for its selective gas adsorption and dye separation.